Pengaruh ketimpangan pendapatan dan kemiskinan terhadap pertumbuhan ekonomi antar pulau di Indonesia - Selamet Rahmadi; Parmadi Parmadi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to find out and analyze the effect of income inequality and poverty on economic growth on each island in Indonesia. To answer these objectives, panel data regression (pooled data) is used. The results of the study show: (1). the best regressions on estimation models are based on the Chow and the Hausman test using the Fixed Effect Model estimation model for each island in Indonesia. (2). Income and poverty inequality negatively affected economic growth in all islands in Indonesia during the 2015-2018.